J ANALISIS TRANSMEDIA STORYTELLING SEBAGAI BENTUK KOLABORASI KARYA AKHIR MAHASISWA PRODI PENYIARAN DAN PERIKLANAN - Pathia, Laelatul; Cempaka, Putri Surya; Zaenab; Widiastuti, Ni Made; Zahrahayati, Erika (ABEC Indonesia, 2023)
The Information and Communication Technology course is a general course that is uniformly applied in study programs under the Publishing Department at Politeknik Negeri Media Kreatif. Among them is the Broadcasting study program and Advertising study program which also provide this courses with similar material, namely transmedia storytelling. Transmedia storytelling refers to the concept of cross-media collaboration with specific goals. The communication resulting from this collaboration is in line with the concept of transmedia storytelling which requires the use of various media to achieve its goals. Thus, the focus of this research is to analyse the concept of transmedia storytelling which is used as an implementation of collaboration across study programs within departments with similar knowledge clusters. By using content analysis method, collaboration is identified in the object of work by students of the two study programs in 2022. The aim of this research is to identify the success of the transmedia storytelling concept as a supporting material for cross-study program collaboration. Researchers analysed using three stages of transmedia storytelling, namely Canon, Apocrypha, and Fanon, so that they could identify the final work based on the level of its development. The results of this study are expected to be an offer in designing collaborative final student projects.